2021
DOI: 10.1126/sciadv.abe6000
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling electron and phonon transport in single-nanowire hybrid materials for high-performance thermoelectrics

Abstract: Organic-inorganic hybrids have recently emerged as a class of high-performing thermoelectric materials that are lightweight and mechanically flexible. However, the fundamental electrical and thermal transport in these materials has remained elusive due to the heterogeneity of bulk, polycrystalline, thin films reported thus far. Here, we systematically investigate a model hybrid comprising a single core/shell nanowire of Te-PEDOT:PSS. We show that as the nanowire diameter is reduced, the electrical conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 58 publications
3
35
1
Order By: Relevance
“…[ 49 ] The outstanding capacity to carry current observed in Nb 1‐ x Ta x S 3 nanofibers can be attributed to the reduced electron scattering rate due to the crystalline structure of this 1D material. [ 50–52 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 49 ] The outstanding capacity to carry current observed in Nb 1‐ x Ta x S 3 nanofibers can be attributed to the reduced electron scattering rate due to the crystalline structure of this 1D material. [ 50–52 ]…”
Section: Resultsmentioning
confidence: 99%
“…[49] The outstanding capacity to carry current observed in Nb 1-x Ta x S 3 nanofibers can be attributed to the reduced elec tron scattering rate due to the crystalline structure of this 1D material. [50][51][52] We also studied the electrical properties of thinfilm Nb 1-x Ta x S 3 on a mica substrate. Figure 3E shows the SEM image of the exfoliated bundle of Nb 1-x Ta x S 3 whiskers.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the underlying morphology of these films, we expect that the thermal conductivity is higher in the in-plane direction than cross-plane. Single wire measurements of the Te-PEDOT:PSS hybrid have shown that the Te core rather than organic shell is the primary conduit of thermal transport along the wire 19 . In a film of composite material, we expect that interfacial resistances between phases (i.e.…”
Section: Discussion Of Model Material Te-pedot:pssmentioning
confidence: 99%
“…Some established strategies that decouple these parameters are nanostructuring, doping, band structure modification, defect engineering, energy filtering effect, complex structure formation, etc. [1][2][3][4] Among the state-of-the-art thermoelectric materials, bismuth telluride is broadly used for developing thermoelectric devices near room temperature. [5][6][7][8][9] Although bismuth telluride alloys have been commercialized, devices based on them show saturation in Z (B5-7% in commercial TEGs) due to the inferior zT (B0.9 at 300 K) of the n-type (Bi 2 (Se-Te) 3 ) composition than the zT (B1.35 at 300 K) of the p-type composition ((Bi-Sb) 2 Te 3 ).…”
Section: Introductionmentioning
confidence: 99%